SEM and EDS Characterisation of Layering TiOx Growth onto the Cutting Tool Surface in Hard Drilling Processes of Ti-Al-V Alloys. (21st September 2011) - Álvarez, M.; Salguero, J.; Sánchez, J. A.; Huerta, M.; Marcos, M.
Abstract : Scanning electron microscopy (SEM) has been used to identify and analyse the secondary adhesion effect precursors formed during the dry drilling processes of Ti-6Al-4V alloy over the rake face and flute of the drilling tools. Subsequent analysis with energy dispersive spectroscopy (EDS) was enabled to distinguish its compositional characteristics. Thus, according to the EDS obtained data, a stratified multi built-up layer (MBUL) composed by TiOx is formed over the rake face of the tool. Furthermore, this multi-layer adhered allows initially the built-up edge (BUE) development close to the edge of the tool by a mechanical adhesion mechanism. In a second step, it is responsible for the formation of a thicker secondary BUL which avoids the chip flow, and it provokes the tool collapse. These mechanisms are different from those observed in the dry machining of other alloys such as steels, nickel-based alloys, or aluminium alloys.